Oral manifestations, risk factors and management strategies of COVID-19 associated mucormycosis in tertiary care hospital - Pankaj Goel; Jitendra Kumar; Anshul Rai; Prateek Shakti; Gunjan Chouksey (Wolters Kluwer Medknow Publications, 2023)
Background: Mucormycosis (black fungus) is an aggressive, life-threatening infectious disease-causing infiltration and by destroying the surrounding bone and soft tissue through vascular thrombosis and subsequent tissue infarction that may reach the brain with fatal complications. Its outbreak has been assessed around the clock during the recent pandemic as post COVID-19 sequelae. Aims: To assess the risk factors, oral signs and symptoms, investigations, treatment and rehabilitation strategies amongst COVID-19 associated mucormycosis patients in a tertiary care hospital. Methods and Material: An observational, pilot study was carried out amongst 30 active or recent COVID-19 associated mucormycosis patients reporting in the Department of Dentistry of a tertiary care hospital in Bhopal over a period of 6 months. Statistical analysis was done using Kolmogorov-Smirnov test using the Statistical Package for Social Sciences, Version 16 software. Results: Study was done on 30 patients (80% males and 20% females) and their median age was 46 years. Predominant risk factor present was diabetes mellitus (90%) and steroid therapy (60%). Prime oral manifestations were toothache (90%), mobile teeth (83%), draining sinus (53%), palatal ulceration (43%) and para-sinusal pain (37%). Conclusions: Mucormycosis can cause serious oro-facial morbidity and mortality in COVID-19 patients. The current management strategy requires early diagnosis, prompt treatment and oral rehabilitation.